Interferensi Bahasa Sunda terhadap Bahasa Indonesia - Purlilaiceu, Purlilaiceu (Jurnal Artikula, 2020)
This research is motivated by the people in Indonesia which consist of various ethnic groups and cultures, each of which has a regional language. This will cause the Indonesian language to receive influence from regional languages, including Sundanese. Like the students of Madrasah Tsanawiah Mathla ul Anwar Banten who use two languages, namely Sundanese as the first language and Indonesian as the second language. The Indonesian language they use is only in learning situations at school, while in their surroundings they use Sundanese as their daily language. Of course the Indonesian they use, especially when students communicate verbally, is still influenced by Sundanese. The problem that the writer examines in this research is the students' oral style, namely how the form of Sundanese phonological interference to Indonesian and the factors causing phonological interference. The method used in this research is descriptive method and research techniques are used to complement this method with literature and recording techniques. The results of the recordings are then made transcript and then interpret the errors, analyze the errors found, and interpret the results of the analysis and conclude them. The results showed that there was the addition of the phoneme h, the replacement of the phoneme f to p, the replacement of the phoneme a to e, the replacement of the phoneme i to e, the replacement of the diphthong au to o, the elimination of the phoneme e, the removal of the phoneme h As for the factors that cause interference by speakers include: bilingualism, lack of loyalty to Indonesian language users, and eliminating rarely used vocabulary.